Non tuberculous Mycobacterial Surgical Site Infections after Laparoscopic Surgery: A Case Series of 37 Patients - Akshant Anil Pathak; Karan Kumar; Vaibhav Aggarwal; Vivek Agrawal (International Journal of Mycobacteriology)
Nontuberculous mycobacterial surgical site infections (SSIs) have a distinct course of disease with diagnosis and treatment presenting challenges. Thirty-seven patients who underwent various procedures and then developed late SSI due to nontuberculous mycobacteria included in this case series. Samples were sent for diagnosis. Patients were started on a regime of levofloxacin with azithromycin. Multiple patients required repeat surgical intervention. The duration of treatment varied from 4 to 6 months. Complete resolution of symptoms occurred in all patients. Nontuberculous mycobacterial infections can be challenging to diagnose and treat. A high degree of clinical suspicion is warranted to limit morbidity.